Perovskite solar cell and preparation method thereof

A flexible encapsulation structure with a sulfuric acid-polyurethane copolymer and zinc oxide nanoparticles enhances the longevity and stability of perovskite solar cells by providing a self-healing barrier against moisture and oxygen, addressing the limitations of traditional encapsulation materials.

CN120322094APending Publication Date: 2025-07-15SHENZHEN PHENOSOLAR TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510415090.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

Perovskite solar cells are extremely sensitive to moisture and oxygen, and traditional packaging materials are difficult to provide effective water-oxygen barriers, resulting in reduced battery performance and short service life.

Method used

The multi-layer flexible packaging structure is adopted, including the outer layer of the flexible substrate and the aluminum oxide layer, and an intermediate layer containing lipoic acid-polyurethane copolymer and zinc oxide nanoparticles, combined with the ionic liquid glue layer to achieve self-healing ability and low water and oxygen transmittance.

Benefits of technology

The service life and stability of perovskite solar cells are significantly improved, and the water and oxygen transmittance is reduced to 10-6gm-2day-1. The self-healing function still maintains more than 90% barrier performance after being triggered at 80℃, and has good flexibility and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120322094A_ABST
    Figure CN120322094A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite solar cell and a preparation method thereof. The perovskite solar cell provided by the invention comprises a cell main body and a packaging structure for packaging the cell main body, the packaging structure comprises an outer layer and a middle layer which are arranged in a stacked mode. The middle layer is arranged between the outer layer and the battery main body; the outer layer comprises a flexible substrate and an aluminum oxide layer which are stacked, and the flexible substrate is arranged between the aluminum oxide layer and the middle layer; the material of the middle layer comprises a lipoic acid-polyurethane copolymer and zinc oxide nanoparticles, and the zinc oxide nanoparticles are dispersed in the lipoic acid-polyurethane copolymer. According to the flexible packaging structure of the perovskite solar cell, low water and oxygen transmittance can be achieved, meanwhile, the flexible packaging structure has the self-repairing capacity, and the service life of the perovskite solar cell can be greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of photovoltaics, and particularly to a perovskite solar cell and a preparation method thereof. Background Art

[0002] Perovskite solar cells have become a research hotspot due to their high conversion efficiency and low preparation cost. However, perovskite materials are extremely sensitive to moisture and oxygen. Once exposed to water and oxygen, the perovskite film is prone to degradation, which in turn leads to a decline in the performance of the perovskite solar cell and even failure. Therefore, it is necessary to encapsulate the perovskite solar cell to provide a relatively stable internal environment for the perovskite solar cell, reduce the performance fluctuations of the battery caused by moisture and oxygen, thereby improving the stability and reliability of the battery and extending the service life of the battery.

[0003] Traditional rigid encapsulation materials such as butyl rubber and epoxy resin have a high water vapor transmission rate (WVTR) and are difficult to meet the long-term stability requirements of perovskite solar cell devices. Flexible encapsulation materials can have a lower water vapor transmission rate compared to rigid encapsulation materials. However, traditional flexible encapsulation materials are prone to irreversible microcracks after bending, which in turn leads to barrier failure. That is, the encapsulation structure of traditional perovskite solar cells has a relatively limited effect on extending the service life of perovskite solar cells. Summary of the Invention

[0004] Based on this, it is necessary to provide a perovskite solar cell and a preparation method thereof. The flexible encapsulation structure of the perovskite solar cell of the present application can not only achieve a low water vapor transmission rate, but also has self-healing ability, which can greatly improve the service life of the perovskite solar cell.

[0005] In a first aspect, the present application provides a perovskite solar cell, including a battery body and an encapsulation structure for encapsulating the battery body; the encapsulation structure includes an outer layer and an intermediate layer arranged in a stacked manner; the intermediate layer is arranged between the outer layer and the battery body; the outer layer includes a flexible substrate and an alumina layer arranged in a stacked manner, and the flexible substrate is arranged between the alumina layer and the intermediate layer; the material of the intermediate layer includes a thiolactic acid-polyurethane copolymer and zinc oxide nanoparticles, and the zinc oxide nanoparticles are dispersed in the thiolactic acid-polyurethane copolymer.

[0006] In some embodiments, in the intermediate layer, the mass of the zinc oxide nanoparticles is 2% - 8% of the mass of the thiolactic acid-polyurethane copolymer.

[0007] In some embodiments, the thickness of the alumina layer is 5nm - 10nm.

[0008] In some of these embodiments, the material of the flexible substrate includes at least one of polyethylene terephthalate and polyimide.

[0009] In some of these embodiments, the particle size of the zinc oxide nanoparticles is 1 nm to 100 nm.

[0010] In some of these embodiments, the thickness of the encapsulation structure is 10 μm to 50 μm.

[0011] In some of these embodiments, the encapsulation structure further includes an ionic liquid adhesive layer, and the ionic liquid adhesive layer is disposed between the intermediate layer and the battery body.

[0012] In some of these embodiments, the material of the ionic liquid adhesive layer includes 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0013] In some of these embodiments, the battery body includes a transparent substrate, a transparent electrode, a first charge extraction layer, a perovskite layer, a second charge extraction layer, and a metal electrode that are sequentially stacked, and the encapsulation structure and the transparent substrate cooperate to encapsulate the transparent electrode, the first charge extraction layer, the perovskite layer, the second charge extraction layer, and the metal electrode therein.

[0014] In some of these embodiments, the material of the transparent electrode includes at least one of ITO, IZO, IWO, ICO, and AZO.

[0015] In some of these embodiments, the perovskite layer includes a material having the following chemical general formula: ABX3, where A is selected from at least one of FA + , MA + , Cs + , and Rb + , B is selected from at least one of Pb 2+ , Sn 2+ , and Sr 2+ , and X is selected from at least one of Cl - , Br - , and I - .

[0016] In some of these embodiments, the material of the metal electrode includes at least one of Al, Ag, Cu, and Au.

[0017] Second aspect, the present application provides a method for preparing a perovskite solar cell, including the following steps:

[0018] Provide a battery body;

[0019] A packaging structure is prepared on the battery body to package the battery body; the packaging structure includes an outer layer and an intermediate layer arranged in a stacked manner; the intermediate layer is arranged between the outer layer and the battery body; the outer layer includes a flexible substrate and an alumina layer arranged in a stacked manner, and the flexible substrate is arranged between the alumina layer and the intermediate layer; the material of the intermediate layer includes a lipoic acid-polyurethane copolymer and zinc oxide nanoparticles, and the zinc oxide nanoparticles are dispersed in the lipoic acid-polyurethane copolymer.

[0020] In some embodiments, the preparation method of the intermediate layer includes the following steps:

[0021] Mix a lipoic acid prepolymer, a polyurethane prepolymer, and zinc oxide nanoparticles to obtain a mixed material;

[0022] The mixed material is subjected to photocuring after coating to obtain the intermediate layer.

[0023] In some embodiments, the alumina layer is prepared by atomic layer deposition.

[0024] In the above perovskite solar cell, the outer layer includes a flexible substrate and an alumina layer arranged in a stacked manner. The flexible substrate has good tensile properties and elastic recovery ability. At the same time, through the alumina layer on its surface, primary water and oxygen barrier properties can be provided. The material of the intermediate layer includes a lipoic acid-polyurethane copolymer and zinc oxide nanoparticles. The lipoic acid-polyurethane copolymer combines the characteristics of lipoic acid-based polymers and the properties of polyurethane. By introducing dynamic covalent bonds such as ester bonds and disulfide bonds, a dynamic crosslinked network can be formed. This network is not permanently fixed, but can dissociate and recombine under certain conditions, which brings self-healing ability to the intermediate layer and can provide secondary barrier to water and oxygen. The zinc oxide nanoparticles dispersed in the lipoic acid-polyurethane copolymer can play a role in ultraviolet absorption and can reduce the photoinduced degradation of the perovskite solar cell. The flexible packaging structure of the perovskite solar cell of the present application can achieve a low water and oxygen transmittance through multi-level water sample barriers, and at the same time has self-healing ability, which can greatly improve the service life of the perovskite solar cell. Description of the Drawings

[0025] Figure 1 It is a schematic structural diagram of a perovskite solar cell provided by an embodiment of the present application;

[0026] Figure 2 It is a schematic structural diagram of a battery body provided by an embodiment of the present application.

[0027] Description of the Reference Numerals

[0028] 10 - Battery body; 11 - Transparent substrate; 12 - Transparent electrode; 13 - First charge extraction layer; 14 - Perovskite layer; 15 - Second charge extraction layer; 16 - Metal electrode; 20 - Ionic liquid adhesive layer; 30 - Intermediate layer; 40 - Flexible substrate; 50 - Aluminum oxide layer. Detailed implementation manners

[0029] To make the above - mentioned objects, features, and advantages of the present application more obvious and understandable, the following provides a detailed description of the specific implementation manners of the present application. Many specific details are set forth in the following description in order to fully understand the present application. However, the present application can be implemented in many other ways different from those described herein. Those skilled in the art can make similar improvements without departing from the connotation of the present application. Therefore, the present application is not limited by the specific embodiments disclosed below.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which this application belongs. The terms used in the description of this application herein are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0031] In the description of this application, it should be understood that the terms "center", "longitudinal", "transverse", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings. They are only for the convenience of describing this application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and thus should not be construed as a limitation of this application.

[0032] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. Thus, features defined with "first" and "second" may explicitly or implicitly include at least one of such features. In the description of this application, "a plurality" means at least two, such as two, three, etc., unless otherwise specifically and clearly defined.

[0033] In this application, unless otherwise clearly specified and defined, terms such as "installed", "connected", "linked", "fixed", etc. shall be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or integrated; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the communication inside two components or the interaction relationship between two components, unless otherwise clearly defined. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0034] Referring to Figure 1 As shown, an embodiment of the present application provides a perovskite solar cell, including a battery body 10 and a packaging structure for packaging the battery body 10; the packaging structure includes an outer layer and an intermediate layer 30 arranged in a stacked manner; the intermediate layer 30 is arranged between the outer layer and the battery body 10; the outer layer includes a flexible substrate 40 and an alumina layer 50 arranged in a stacked manner, and the flexible substrate 40 is arranged between the alumina layer 50 and the intermediate layer 30; the material of the intermediate layer 30 includes a lipoic acid-polyurethane copolymer and zinc oxide nanoparticles, and the zinc oxide nanoparticles are dispersed in the lipoic acid-polyurethane copolymer.

[0035] In the above perovskite solar cell, the outer layer includes a flexible substrate 40 and an alumina layer 50 arranged in a stacked manner. The flexible substrate 40 has good tensile properties and elastic recovery ability. At the same time, through the alumina layer 50 on its surface, primary water and oxygen barrier performance can be provided. The material of the intermediate layer 30 includes a lipoic acid-polyurethane copolymer and zinc oxide nanoparticles. The lipoic acid-polyurethane copolymer combines the characteristics of lipoic acid-based polymers and the properties of polyurethane, and a dynamic cross-linked network can be formed by introducing dynamic covalent bonds such as ester bonds and disulfide bonds. This network is not permanently fixed, but can dissociate and recombine under certain conditions, which brings self-healing ability to the intermediate layer 30 and can provide secondary barrier to water and oxygen. The zinc oxide nanoparticles dispersed in the lipoic acid-polyurethane copolymer can play the role of ultraviolet absorption and can reduce the photoinduced degradation of the perovskite solar cell. The flexible packaging structure of the perovskite solar cell of the present application can achieve a low water and oxygen transmittance through multi-level water sample barriers, and at the same time has self-healing ability, which can greatly improve the service life of the perovskite solar cell.

[0036] The water and oxygen transmittance (WVTR) of the perovskite solar cell of the present application is less than 10 -6 gm -2 day -1 , far less than that of traditional packaging materials, which is 10 -6 gm -2 day -1The WVTR can meet the requirements for long-term use of perovskite solar cells. Meanwhile, the perovskite solar cell of this application has a self-healing function and can trigger self-healing under the conditions of 80 °C / 5 min. After repair, it can still maintain a barrier performance greater than 90%. Meanwhile, the perovskite solar cell of this application can be a flexible perovskite solar cell, that is, a perovskite solar cell using a flexible substrate. When the encapsulation structure of this application is used to encapsulate a flexible perovskite solar cell, the flexible perovskite solar cell can have good flexible reliability. The efficiency retention rate can still be greater than 95% after 500 cycles at a bending radius of 3 mm.

[0037] In some embodiments, in the intermediate layer 30, the mass of zinc oxide nanoparticles is 2% to 8% of the mass of the lipoic acid-polyurethane copolymer.

[0038] Optionally, in the intermediate layer 30, the mass of zinc oxide nanoparticles is 2%, 3%, 4%, 5%, 6%, 7% or 8% of the mass of the lipoic acid-polyurethane copolymer. Or, in the intermediate layer 30, the percentage of the mass of zinc oxide nanoparticles in the lipoic acid-polyurethane copolymer can also be within the range between any two of the above mass percentages.

[0039] In some embodiments, the thickness of the alumina layer 50 is 5 nm to 10 nm.

[0040] Within the range of the thickness of the above alumina layer 50, it is convenient to take into account the better water sample barrier performance and light transmittance of the alumina layer 50. Optionally, the thickness of the alumina layer 50 is 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm. Or, the thickness of the alumina layer 50 can also be within the range between any two of the above thicknesses.

[0041] In some embodiments, the light transmittance of the alumina layer 50 is more than 90%.

[0042] In some embodiments, the material of the flexible substrate 40 includes at least one of polyethylene terephthalate and polyimide.

[0043] Polyethylene terephthalate (PET) is a common flexible material with characteristics such as being thin, transparent, flexible and having good stretchability. The PET film has high strength and elastic recovery ability. It has good light resistance and good chemical resistance. The polyimide (PI) film material is prepared by a condensation reaction of one or several binary anhydride monomers and binary amine monomers in a certain molar ratio. Due to its rigid aromatic heterocyclic structure, this material has good heat resistance. PI also has excellent thermal stability, good mechanical properties, solvent resistance and low dielectric constant, and it has high transparency.

[0044] In some of these embodiments, the particle size of the zinc oxide nanoparticles is 1 nm to 100 nm.

[0045] Due to the size effect, zinc oxide nanoparticles with a particle size of 1 nm to 100 nm exhibit physical and chemical properties different from those of traditional zinc oxide, including an enhanced specific surface area, altered surface energy states, and quantum size effects. It can play a role in enhancing ultraviolet absorption and reducing the light decay of perovskite. Optionally, the particle size of the zinc oxide nanoparticles is 1 nm, 2 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 80 nm, or 100 nm, or alternatively, the particle size of the zinc oxide nanoparticles can also be within the range between any two of the above particle sizes.

[0046] In some of these embodiments, the thickness of the intermediate layer 30 is 15 μm to 25 μm.

[0047] Optionally, the thickness of the intermediate layer 30 is 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, or 25 μm, or alternatively, the thickness of the intermediate layer 30 can also be within the range between any two of the above thicknesses.

[0048] In some of these embodiments, the thickness of the encapsulation structure is 10 μm to 50 μm.

[0049] Optionally, the thickness of the encapsulation structure is 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or 50 μm, or alternatively, the thickness of the encapsulation structure can also be within the range between any two of the above thicknesses.

[0050] In some of these embodiments, the encapsulation structure further includes an ionic liquid adhesive layer 20, and the ionic liquid adhesive layer 20 is disposed between the intermediate layer 30 and the battery body 10.

[0051] The ionic liquid adhesive layer 20 can melt at a lower temperature and remain in a liquid state. Combining the special chemical properties of ionic liquids, it may provide better bonding performance, especially on materials that are not friendly to traditional hot melt adhesives. The ionic liquid adhesive layer 20 can be attached to the battery surface at a low temperature (60 °C), fill interface defects, and passivate the perovskite surface. At the same time, the ionic liquid adhesive layer 20 also has high transparency, stretchability, mechanical strength, and room temperature self-healing ability.

[0052] In some of these embodiments, the thickness of the ionic liquid adhesive layer 20 is 2 μm to 10 μm.

[0053] Optionally, the thickness of the ionic liquid adhesive layer 20 is 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm. Alternatively, the thickness of the ionic liquid adhesive layer 20 can also be within the range between any two of the above thicknesses.

[0054] In some embodiments, the material of the ionic liquid adhesive layer 20 includes 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide.

[0055] Referring Figure 2 As shown, in some embodiments, the battery body 10 includes a transparent substrate 11, a transparent electrode 12, a first charge extraction layer 13, a perovskite layer 14, a second charge extraction layer 15, and a metal electrode 16 that are sequentially stacked. The encapsulation structure and the transparent substrate 11 cooperate to encapsulate the transparent electrode 12, the first charge extraction layer 13, the perovskite layer 14, the second charge extraction layer 15, and the metal electrode 16 therein.

[0056] In some embodiments, the material of the transparent electrode 12 includes at least one of ITO, IZO, IWO, ICO, and AZO.

[0057] In some embodiments, the perovskite layer 14 includes a material having the following chemical general formula: ABX3, where A is selected from at least one of FA + 、MA + 、Cs + and Rb + ; B is selected from at least one of Pb 2+ 、Sn 2+ and Sr 2+ ; and X is selected from at least one of Cl - 、Br - and I - .

[0058] In some embodiments, the material of the metal electrode 16 includes at least one of Al, Ag, Cu, and Au.

[0059] In some embodiments, the first charge extraction layer 13 is a hole transport layer, and the second charge extraction layer 15 is an electron transport layer.

[0060] In some embodiments, the first charge extraction layer 13 is an electron transport layer, and the second charge extraction layer 15 is a hole transport layer.

[0061] In some embodiments, the material of the hole transport layer includes at least one of 2PACz, NiO, PTAA, and Spiro-OMeTAD.

[0062] In some of these embodiments, the material of the electron transport layer includes at least one of fullerenes and their derivatives, SnO2, TiO2, ZnO, and In2O3.

[0063] In some of these embodiments, the transparent substrate 11 is a flexible transparent substrate 11.

[0064] Another embodiment of the present application provides a method for preparing a perovskite solar cell, comprising the following steps:

[0065] Provide a battery body 10;

[0066] Prepare an encapsulation structure on the battery body 10 to encapsulate the battery body 10; the encapsulation structure includes an outer layer and an intermediate layer 30 arranged in a stacked manner; the intermediate layer 30 is arranged between the outer layer and the battery body 10; the outer layer includes a flexible substrate 40 and an alumina layer 50 arranged in a stacked manner, and the flexible substrate 40 is arranged between the alumina layer 50 and the intermediate layer 30; the material of the intermediate layer 30 includes a thiolactic acid-polyurethane copolymer and zinc oxide nanoparticles, and the zinc oxide nanoparticles are dispersed in the thiolactic acid-polyurethane copolymer.

[0067] In some of these embodiments, the method for preparing the intermediate layer 30 includes the following steps:

[0068] Mix a thiolactic acid prepolymer, a polyurethane prepolymer, and zinc oxide nanoparticles to obtain a mixed material;

[0069] The mixed material is coated and then photocured to obtain the intermediate layer 30.

[0070] In some of these embodiments, the alumina layer 50 is prepared by atomic layer deposition.

[0071] In some of these embodiments, the method for preparing a perovskite solar cell includes the following steps:

[0072] Provide a battery body 10, the battery body 10 includes a transparent substrate 11, a transparent electrode 12, a first charge extraction layer 13, a perovskite layer 14, a second charge extraction layer 15, and a metal electrode 16 arranged in a stacked manner in sequence;

[0073] Spray an ionic liquid glue on the battery body 10 so that the ionic liquid glue cooperates with the transparent substrate 11 to encapsulate the transparent electrode 12, the first charge extraction layer 13, the perovskite layer 14, the second charge extraction layer 15, and the metal electrode 16;

[0074] Provide a flexible substrate 40, and prepare an alumina layer 50 on one surface of the flexible substrate 40 by atomic layer deposition;

[0075] Mix the lipoic acid prepolymer, polyurethane prepolymer, and zinc oxide nanoparticles to obtain a mixed material. Coat the mixed material on the opposite surface of the surface of the flexible substrate 40 provided with the alumina layer 50, and then perform ultraviolet curing to obtain a composite layer having an outer layer and an intermediate layer 30;

[0076] Attach the composite layer to the battery body 10, and make the intermediate layer 30 contact the ionic liquid adhesive layer 20. Heat to bond the intermediate layer 30 and the ionic liquid adhesive layer 20 to obtain a perovskite solar cell having an encapsulation structure.

[0077] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered to be within the scope described in this specification.

[0078] The above-described embodiments only represent several implementation manners of the present application. The description is relatively specific and detailed, but it should not be construed as a limitation on the scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present application, several deformations and improvements can still be made, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application should be subject to the appended claims, and the specification and drawings can be used to explain the content of the claims.

Claims

1. A perovskite solar cell, characterized in that, It includes a battery body and a packaging structure for encapsulating the battery body; the packaging structure includes an outer layer and an intermediate layer arranged in a stacked manner; the intermediate layer is arranged between the outer layer and the battery body; the outer layer includes a flexible substrate and an alumina layer arranged in a stacked manner, and the flexible substrate is arranged between the alumina layer and the intermediate layer; the material of the intermediate layer includes a thiolactic acid-polyurethane copolymer and zinc oxide nanoparticles, and the zinc oxide nanoparticles are dispersed in the thiolactic acid-polyurethane copolymer.

2. The perovskite solar cell according to claim 1, wherein In the intermediate layer, the mass of the zinc oxide nanoparticles is 2% - 8% of the mass of the thiolactic acid-polyurethane copolymer.

3. The perovskite solar cell according to claim 1, characterized in that, The perovskite solar cell satisfies at least one of the following characteristics: (1) The thickness of the alumina layer is 5 nm - 10 nm; (2) The material of the flexible substrate includes at least one of polyethylene terephthalate and polyimide; (3) The particle size of the zinc oxide nanoparticles is 1 nm - 100 nm; (4) The thickness of the packaging structure is 10 μm - 50 μm.

4. The perovskite solar cell according to claim 1, wherein The packaging structure further includes an ionic liquid glue layer, and the ionic liquid glue layer is arranged between the intermediate layer and the battery body.

5. The perovskite solar cell according to claim 4, characterized in that, The material of the ionic liquid glue layer includes 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

6. The perovskite solar cell according to any one of claims 1 to 5, characterized in that, The battery body includes a transparent substrate, a transparent electrode, a first charge extraction layer, a perovskite layer, a second charge extraction layer, and a metal electrode arranged in a stacked manner in sequence, and the packaging structure and the transparent substrate cooperate to encapsulate the transparent electrode, the first charge extraction layer, the perovskite layer, the second charge extraction layer, and the metal electrode therein.

7. The perovskite solar cell according to claim 6, wherein, The battery body satisfies at least one of the following characteristics: (1) The material of the transparent electrode includes at least one of ITO, IZO, IWO, ICO, and AZO; (2) The perovskite layer comprises a material having the following chemical general formula: ABX3, wherein A is selected from FA + , MA + , Cs + and Rb + , at least one of which; B is selected from Pb 2+ , Sn 2+ and Sr 2+ , at least one of which; X is selected from Cl - , Br - and I - , at least one of which; (3) The material of the metal electrode includes at least one of Al, Ag, Cu, and Au.

8. A method for preparing a perovskite solar cell, characterized in that, It includes the following steps: Provide a battery body; Prepare a packaging structure on the battery body to encapsulate the battery body; the packaging structure includes an outer layer and an intermediate layer arranged in a stacked manner; the intermediate layer is arranged between the outer layer and the battery body; the outer layer includes a flexible substrate and an alumina layer arranged in a stacked manner, and the flexible substrate is arranged between the alumina layer and the intermediate layer; the material of the intermediate layer includes a thiolactic acid-polyurethane copolymer and zinc oxide nanoparticles, and the zinc oxide nanoparticles are dispersed in the thiolactic acid-polyurethane copolymer.

9. The method for preparing a perovskite solar cell according to claim 8, characterized in that, The preparation method of the intermediate layer includes the following steps: Mix a thiolactic acid prepolymer, a polyurethane prepolymer, and zinc oxide nanoparticles to obtain a mixed material; The mixed material is coated and then subjected to photocuring to obtain the intermediate layer.

10. The preparation method of the perovskite solar cell according to claim 8, characterized in that, The alumina layer is prepared by atomic layer deposition.